Meaningful healthcare experience design : improving care for all generations - Goodwin, Scott (Routledge, 2020)
"This book offers a new perspective on improving healthcare that draws inspiration from sources as diverse as American healthcare history, Lean Six Sigma, patient experience, employee engagement, clinical microsystems, physician burnout and industrial design thinking. This work focuses on the three values streams that form the foundation of all healthcare service processes: healthcare-worker value stream, patient value stream and organizational process. The interaction of patients and healthcare workers in the context of these three value streams creates the meaningful experience that is essential to healing and to the success of healthcare organizations. Meaningful Experience Design (MXD) guides the work of designing these value streams and improving them to promote daily experiences that are meaningful and healing for both patients and healthcare workers"--